2002
DOI: 10.1074/jbc.m205042200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New Type of Phosphopantetheinyl Transferase for Fatty Acid and Siderophore Synthesis in Pseudomonas aeruginosa

Abstract: Phosphopantetheinyl-dependent carrier proteins are part of fatty-acid synthases (primary metabolism), polyketide synthases, and non-ribosomal peptide synthetases (secondary metabolism). For these proteins to become functionally active, they need to be primed with the 4-phosphopantetheine moiety of coenzyme A by a dedicated phosphopantetheine transferase (PPTase). Most organisms that employ more than one phosphopantetheinyl-dependent pathway also have more than one PPTase. Typically, one of these PPTases is opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 33 publications
8
102
0
Order By: Relevance
“…Recently, both prokaryotic and eukaryotic organisms have been identified that appear to use a single PPTase for servicing carrier proteins associated with both primary and secondary metabolic pathways. For example, Marahiel's team have reported that Pseudomonas aeruginosa harbors but one PPTase that is responsible for the phosphopantetheinylation of the ACP required for fatty acid biosynthesis and the PCPs required for biosynthesis of the non-ribosomally produced peptide siderophores pyoverdin and pyochelin (29). In common with the situation in humans, the PPTase of P. aeruginosa is of the high molecular mass, monomeric class and, of course, this enzyme too, displays a very broad substrate specificity.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, both prokaryotic and eukaryotic organisms have been identified that appear to use a single PPTase for servicing carrier proteins associated with both primary and secondary metabolic pathways. For example, Marahiel's team have reported that Pseudomonas aeruginosa harbors but one PPTase that is responsible for the phosphopantetheinylation of the ACP required for fatty acid biosynthesis and the PCPs required for biosynthesis of the non-ribosomally produced peptide siderophores pyoverdin and pyochelin (29). In common with the situation in humans, the PPTase of P. aeruginosa is of the high molecular mass, monomeric class and, of course, this enzyme too, displays a very broad substrate specificity.…”
Section: Discussionmentioning
confidence: 98%
“…4b). Note that although Sfp has been suggested to exhibit substrate preference towards the CPs from secondary metabolic pathways [22], the higher modification efficiency for EACP in comparison to the three CPs from secondary metabolic pathways probably reflects the variation among different FAS-ACPs. Indeed, very different catalytic efficiency has been observed for Sfp towards PCPs from different species, including tycc3-PCP from B. subtilis (k cat = 96 min À1 , k cat /K m = 22.6 min À1 lM À1 ) and GPCP (GrsA-PCP) from B. brevis (k cat = 10.3 min À1 , k cat / K m = 2.5 min À1 lM À1 ) [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the division within the Sfp-type PPTases reflects a functional difference. However, although EntD and PcpS both fall within the Group II Sfp-type PPTases, only one of them (PcpS) can substitute for AcpS (Flugel et al, 2000;Finking et al, 2002;Barekzi et al, 2004). Similarly, Sfp and PcpS are members of different PPTase groups, but both can substitute for AcpS ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a Bacillus subtilis acpS mutant supports fatty acid biosynthesis, and Bacillus subtilis Sfp will modify E. coli or Bacillus subtilis apo-ACP in vitro (Quadri et al, 1998b;Mootz et al, 2001). In the case of Pseudomonas aeruginosa, the cross-reactivity of the Sfp-type PPTase is obligatory, as only the Sfp-type PPTase (PcpS) is present (Finking et al, 2002;Barekzi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%